Cardiac Structural and Functional Consequences of Amyloid Deposition by Cardiac Magnetic Resonance and Echocardiography and Their Prognostic Roles - Knight, Daniel S.; Zumbo, Giulia; Barcella, William; Steeden, Jennifer A.; Muthurangu, Vivek; Martinez-Naharro, Ana; Treibel, Thomas A.; Abdel-Gadir, Amna; Bulluck, Heerajnarain; Kotecha, Tushar; Francis, Rohin; Rezk, Tamer; et al. (JACC. Cardiovascular imaging, 2019)
This cross-sectional study aimed to describe the functional and structural cardiac abnormalities that occur across a spectrum of cardiac amyloidosis burden and to identify the strongest cardiac functional and structural prognostic predictors in amyloidosis using cardiac magnetic resonance (CMR) and echocardiography. Cardiac involvement in light chain and transthyretin amyloidosis is the main driver of prognosis and influences treatment strategies. Numerous measures of cardiac structure and function are assessed by multiple imaging modalities in amyloidosis. A total f 322 subjects (311 systemic amyloidosis and 11 transthyretin gene mutation carriers) underwent comprehensive CMR and transthoracic echocardiography. The probabilities of 11 commonly measured structural and functional cardiac parameters being abnormal with increasing cardiac amyloidosis burden were evaluated. Cardiac amyloidosis burden was quantified using CMR-derived extracellular volume. The prognostic capacities of these parameters to predict death in amyloidosis were assessed using Cox proportional hazards models. Left ventricular mass and mitral annular plane systolic excursion by CMR along with strain and E/e’ by echocardiography have high probabilities of being abnormal at low cardiac amyloid burden. Reductions in biventricular ejection fractions and elevations in biatrial areas occur at high burdens of infiltration. The probabilities of indexed stroke volume, myocardial contraction fraction, and tricuspid annular plane systolic excursion (TAPSE) being abnormal occur more gradually with increasing extracellular volume. Ninety patients (28%) died during a median follow-up of 22 months (interquartile range: 10 to 38 months). Univariable analysis showed that all imaging markers studied significantly predicted outcome. Multivariable analysis showed that TAPSE (hazard ratio: 1.46; 95% confidence interval: 1.16 to 1.85; p < 0.01) and indexed stroke volume (hazard ratio: 1.24; 95% confidence interval: 1.04 to 1.48; p < 0.05) by CMR were the only independent predictors of mortality. Specific functional and structural abnormalities characterize different burdens of cardiac amyloid deposition. In a multimodality imaging assessment of a large cohort of amyloidosis patients, CMR-derived TAPSE and indexed stroke volume are the strongest prognostic cardiac functional markers. [Display omitted]